Pengaruh Gaya Kepemimpinan dan Motivasi Terhadap Efektivitas Kerja Dengan Disiplin Kerja Sebagai Variabel Intervening - Dita Fariska; Kusuma Chandra Kirana; Didik Subiyanto (Coopetition : Jurnal Ilmiah Manajemen, 2022)
This study aims to determine and examine the effect of Leadership Style, work motivation on work effectiveness with Work Discipline as an intervening variable. This study uses quantitative research methods. The population in this study is all employees and their partners in the BUMDes Maju Mandiri Office. This study consisted of 60 employees. The sampling technique in this study used a saturated sampling technique, i.e. all the population was sampled. The analytical method used in this study used multiple linear regression analysis. The results in this study indicate that partially leadership style affects work discipline. Work motivation has no effect on work discipline, leadership style has no effect on work effectiveness, work motivation has no effect on work effectiveness, and simultaneously or together work discipline has an effect on work effectiveness.